Atividade antibacteriana do óleo essencial do cravo da índia (Syzygium aromaticum) frente a staphylococcus pseudintermedius resistentes e sensíveis a meticilina isolados de cães com otite externa - Freitas, Vanessa Danielle de (2019)
Infections caused by methicillin-resistant Staphylococcus pseudintermedius (MRSP) have been increasingly common in veterinary medicine and are recognized as a growing threat to human health. The indiscriminate use of antibiotics by animal owners ends up aggravating this situation and resulting in a compromise in the effectiveness of treatment, requiring the search for alternative treatment methods in the market. Thus, the objective of this work was to evaluate the potential inhibitory effect of clove essential oil (Syzygium aromaticum) on the growth of methicillin-resistant and sensitive S. pseudintermedius. In this study, 43 isolates of S. pseudintermedius obtained from dogs with otitis externa were evaluated. The samples were identified by phenotypic and molecular tests. MRSPs were identified by oxacillin and cefoxitin resistance by the agar gel disk diffusion technique and by detection of the mecA resistance gene by conventional PCR technique. Antimicrobial sensitivity profile and multiresistance evaluation were performed using 22 antimicrobials corresponding to 13 antimicrobial classes. Of the 43 isolates, 27.9% were resistant to oxacillin and 16.2% to cefoxitin and in 30.2% the presence of mecA gene was detected. The effectiveness of the essential oil was evaluated by the microdilution technique to determine the minimum inhibitory concentration (MIC) of S. aromaticum. After microdilution, clove essential oil was observed to have a MIC and mean minimum bactericidal concentration (CBM) of 6.34mg/mL (± 4.51) between the total of MRSP and methicillin-susceptible S. pseudintermedius (MSSP) isolates tested. It was concluded that the clove essential oil proved to have antimicrobial action and was able to inhibit the growth of both resistant and methicillin sensitive S. pseudintermedius isolates.